The danger of a single story about Fulani pastoralists - Mark Moritz; Mamediarra Mbacke (Pastoralism, 2022)
Abstract In the last few years, an increasing number of articles, reports, websites, and official documents have been published with narratives that link Fulani pastoralists to insecurity in West and Central Africa. In this article, we critically analyse one of these documents: a legislation factsheet from the United States Commission on International Religious Freedom (USCIRF) titled Factsheet: Fulani Communities that was published in September 2020. We focus our analysis on this factsheet because it is an official document from a US government entity that aims to inform policy-makers, it contains problematic narratives that are emblematic of larger discourses about Fulani pastoralists, and it links to a number of questionable sources. We critically reviewed the narratives in the factsheet and the linked sources. We found that even though it aims to be fair and balanced, the factsheet is biased against Fulani pastoralists, primarily because it links one single group to violence and religious tension and its use of problematic sources. In conclusion, we find that the factsheet perpetuates a single story or stereotype about Fulani pastoralists and thereby fuels existing inflammatory rhetoric that will likely increase insecurity, rather than contribute to peace and stability in the region.